2008
DOI: 10.1140/epje/i2008-10405-5
|View full text |Cite
|
Sign up to set email alerts
|

Tetracene film morphology: Comparative atomic force microscopy, X-ray diffraction and ellipsometry investigations

Abstract: X-ray diffraction, atomic force microscopy and spectroscopic ellipsometry were used to study tetracene thin films as a function of deposition rate. A comparative analysis of the thickness and roughness values allows for detailed modelling of the film morphology. An interdigitated growth mode is established for the coexisting thin film and bulk phases. By comparison with the respective quinone-derivative of tetracene, we were additionally able to identify reaction products by their optical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Due to our wide spectral range of analysis, we also extract interband transition at 4.406 eV, not reported previously in the literature. This interband transition is close to the transition at 4.07 eV observed for bulk phase tetracene [32]. Fig.…”
Section: Ellipsometric Characterizationsupporting
confidence: 84%
“…Due to our wide spectral range of analysis, we also extract interband transition at 4.406 eV, not reported previously in the literature. This interband transition is close to the transition at 4.07 eV observed for bulk phase tetracene [32]. Fig.…”
Section: Ellipsometric Characterizationsupporting
confidence: 84%
“…19 However, in thin polycrystalline Tc films two polymorphs might co-exist leading to different time scales. 25 The subsequent rise observed on a 40 ps timescale, see Figures 9 and 10, represents an increasing triplet yield due to thermally activated SEF S 1 + E → 1 (T 1 T 1 ) → 2T 1 . Comparable values of τ 1 , τ 2 , and τ 3 , describing the ESA signal's temporal dynamics, are obtained for both the 200 nm and 300 nm thick crystals excited at 387 nm, see Table III.…”
Section: Excited State Absorption and Singlet Exciton Fissionmentioning
confidence: 94%
“…8,9 In order to understand the fundamental electronic properties and their dynamics upon photo-excitation steady state absorption, [10][11][12] emission, 10,[13][14][15][16] photoemission, 17 and transient absorption [18][19][20][21][22][23][24][25] spectroscopy studies on both Tc crystals and Tc polycrystalline thin films have been used.…”
Section: Introductionmentioning
confidence: 99%
“…The azimuthal scans were performed at room temperature. In X‐ray reflectivity measurements the authors found two closely related crystal polymorphs, which were observed in previous studies (see Supporting Information) . For the data analysis presented here the authors chose Bragg reflections of the bulk phase .…”
Section: Methodsmentioning
confidence: 62%
“…While NLC films are usually nonabsorbing, tetracene molecules absorb a significant portion of the laser light and every molecule that is not yet photoaligned is repeatedly excited on the 100 ms time scale during LDSA growth (5 W cm −2 , 532 nm) . This excitation energy is largely transferred into optothermal heating, because singlet fission is a dominant decay channel of excitations and the quantum efficiency of the first excited state S 1 luminescence is below 1% .…”
mentioning
confidence: 99%